MULTILAYER RACISMS AS REPRESENTED IN ARUNDHATI ROY’S THE GOD OF SMALL THINGS - Dwi Fatmawati; Irana Astutiningsih (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2020)
This article discusses racism in India as illustrated in Arundhati Roy’s The God of Small Things. The novel contains racism issues in India in 19th century. In the novel, not only is racism experienced by coloured people as a result of white people discriminating them, but also among the coloured people themselves, experienced by those considered inferior based on caste. The research aims at figuring out how racism is constructed in The God of Small Things as well as knowing the ideological position of the author. Hence, Hall’s representation theory is used in this research focusing on discursive approach. The result shows that the author criticizes racism and people’s classification based on caste.